2001
DOI: 10.1016/s0896-6273(01)00266-5
|View full text |Cite
|
Sign up to set email alerts
|

Differential Control of Clustering of the Sodium Channels Nav1.2 and Nav1.6 at Developing CNS Nodes of Ranvier

Abstract: Na(v)1.6 is the main sodium channel isoform at adult nodes of Ranvier. Here, we show that Na(v)1.2 and its beta2 subunit, but not Na(v)1.6 or beta1, are clustered in developing central nervous system nodes and that clustering of Na(v)1.2 and Na(v)1.6 is differentially controlled. Oligodendrocyte-conditioned medium is sufficient to induce clustering of Na(v)1.2 alpha and beta2 subunits along central nervous system axons in vitro. This clustering is regulated by electrical activity and requires an intact actin c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
240
0
3

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 271 publications
(254 citation statements)
references
References 70 publications
11
240
0
3
Order By: Relevance
“…We proposed that axonal ␤1 subunits located at the nodal-paranodal border may interact in cis with axonal contactin molecules in the paranode or in trans with glial Nf155 molecules at the nodal-paranodal border region. Alternatively, because we have also shown ␤1 expression in oligodendrocytes (53), it is possible that glial ␤1 subunits may interact in trans with axonal ␤1 subunits, in cis with glial Nf155, or in trans with axonal contactin molecules. In the present study, we tested the hypothesis that ␤1 interacts with Nf155 and showed that these molecules interact in our assay.…”
Section: Discussionmentioning
confidence: 84%
“…We proposed that axonal ␤1 subunits located at the nodal-paranodal border may interact in cis with axonal contactin molecules in the paranode or in trans with glial Nf155 molecules at the nodal-paranodal border region. Alternatively, because we have also shown ␤1 expression in oligodendrocytes (53), it is possible that glial ␤1 subunits may interact in trans with axonal ␤1 subunits, in cis with glial Nf155, or in trans with axonal contactin molecules. In the present study, we tested the hypothesis that ␤1 interacts with Nf155 and showed that these molecules interact in our assay.…”
Section: Discussionmentioning
confidence: 84%
“…Based on their physiological properties, it would be expected that Na v 1.2 and Na v 1.6, which both produce rapidly activating and inactivating currents (32)(33)(34), would both support actionpotential generation. Consistent with this, Na v 1.6 is the predominant sodium channel at nodes of Ranvier (2), whereas Na v 1.2 is expressed along premyelinated CNS axons (3,22), which are known to conduct action potentials (35,36). There is evidence suggesting that some sodium channels, when colocalized with the NCX, can contribute to axonal degeneration.…”
Section: Discussionmentioning
confidence: 86%
“…During the development of myelinated CNS tracts, Na v 1.2 channels [which are also present along unmyelinated axons (3,20,21)] are initially expressed along premyelinated axons, with a transition to clusters of Na v 1.6 at mature nodes of Ranvier (3,22). In dysmyelinated axons from Shiverer mice, Na v 1.2 channels are retained, and Na v 1.6 is not expressed (3,23), and in axons from Plp͞Ϫ mice, which myelinate normally and then lose their myelin, there is a loss of Na v 1.6 clustering and increased expression of Na v 1.2 (24).…”
mentioning
confidence: 99%
“…In the CNS, oligodendroglia are known to similarly direct nodal Na ϩ channel clustering but are devoid of ERM proteins (26). We hypothesize that JN serves a CNS function similar to that of the ERM proteins in the PNS, based on its putative ERM-like actin-binding domain, its influence on oligodendroglial-process outgrowth͞branching to approach the putative target axons, and its selective positioning to the juxtanodal terminal loops next to the node.…”
Section: Jn: An Oligodendroglia Marker Of a Previously Unidentified Pmentioning
confidence: 97%